HYDROLOGY OF A DRAINAGE BASIN ON THE ALASKAN COASTAL PLAIN. - Brown,Jerry; Dingman,S. Lawrence; Lewellen,Robert I. (1968)
A 4-summer hydrologic record from a 1.6-sq km drainage basin at Barrow, Alaska is analyzed. The watershed, a drained lake basin, is underlain by continuous permafrost within 0.3 m of the tundra surface and is covered by ice-wedge polygons and numerous small shallow ponds. Considerable variations from the 20-yr means of summer climate (thaw period 88 days, precipitation 67 mm) are represented in the data; 1963 - cold, extremely wet; 1964 - cold, extremely dry; 1965 - cool, dry; 1966 - cool, wet. Runoff varied greatly from storm to storm, occurring primarily through and over the tundra mat and through an intricate system of polygonal troughs and ponds. As a result of the subdued coastal topography, varying areas (0.3 sq km to 1.6 sq km) contribute to runoff from different storms. Analyses of hydrographs revealed: (1) lag times generally from 3 to 10 hr; (2) recession constants of about 50 hr, but occasionally as much as 160 hr; and (3) runoff from individual storms between 1 and 70%. About 5% of the thaw season precipitation normally runs off. Comparison of total thaw season precipitation between the U.S. Weather Bureau and a shielded gage located on the watershed indicated no major differences. Precipitation chemistry showed no correlation with storm direction. Assuming all winter precipitation runs off, and the data are spatially and temporally representative, about 50% of the measured annual precipitation in this region runs off into the Arctic Ocean. (Author)